The Short-Run Macro Implications of School and Child-Care Closures - Nicola Fuchs-Schündeln; Moritz Kuhn; Michèle Tertilt (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
The COVID19 crisis has hit labor markets. School and child-care closures have put families with children in challenging situations. We look at Germany and quantify the macroeconomic importance of working parents. We document that 26 percent of the German work force have children aged 14 or younger and estimate that 11 percent of workers and 8 percent of all working hours are affected if schools and child-care centers remain closed. In most European countries,the share of affected working hours is even higher. Policies to restart the economy have to accommodate the concerns of these families.
Keywords: 330; COVID-19; labor market; children; child-care; parents; workforce